Growth Response of Bambara Groundnut to the Application of Rhizobium sp. and Pseudomonas sp. in Matriconditioning and Nitrogen-Phosphate Fertilization - Umadi, Sarah Sakinah; Ilyas, Satriyas; Widyastuti, Rahayu (Journal of Tropical Crop Science, 2025)
Bambara groundnut has the potential to be an alternative food source of protein and carbohydrates. However, the quality of the seeds is not guaranteed, which can affect plant growth. The experiment aimed to determine the growth response of Bambara groundnut to the application of nitrogen fixation bacteria (Rhizobium sp.) and phosphate solubilizing bacteria (Pseudomonas sp.) integrated into matriconditioning and nitrogen-phosphate (NP) fertilizer. The experiment was conducted in Situraja-District, Sumedang Regency, West Java, Indonesia from November 2020 to April 2021. The experiment was arranged in a split-plot randomized complete block design replicated three times. The main plot was NP fertilizer level (0, 50, and 100% of recommended dose), and the sub-plot was seed invigoration (untreated, matriconditioning + Rhizobium KPB2 + Pseudomonas BPF9, and matriconditioning + Rhizobium KPB5 + Pseudomonas BPF9). Corncob biochar was used as the carrier in matriconditioning. The seed invigoration treatments using matriconditioning + Pseudomonas BPF9 + Rhizobium either KPB2 or KPB5 isolate significantly improved the plant growth (field emergence, plant height, leaf number, canopy diameter, and leaf chlorophyll content). Furthermore, when these invigoration treatments were accompanied by chicken manure 2 t.ha-1 significantly increased the leaf number without adding NP fertilizer.